The heparan sulphate proteoglycan Syndecan‐1 (CD138) regulates tumour progression in a 3D model of ductal carcinoma in situ of the breast. Issue 10 (19th May 2022) - D'Arcy, Christopher; Zimmermann, Clarissa Constanze; Espinoza‐Sanchez, Nancy Adriana; Greve, Burkhard; Schmidt, Annika; Kiesel, Ludwig; von Wahlde, Marie‐Kristin; Götte, Martin
Abstract: Ductal carcinoma in situ (DCIS) is a form of breast cancer that is restricted to the lactiferous ducts and has not yet invaded the surrounding breast tissue. Dysregulation of the transmembrane heparan sulphate proteoglycan Syndecan‐1 (Sdc‐1) plays a role in tumour progression of invasive breast cancer (IBC). In DCIS, Sdc‐1, c‐Met and E‐cadherin are part of a proangiogenic expression signature. In this study, we employed a siRNA knockdown approach in the DCIS model cell line MCF10A DCIS.com to investigate a potential connection between Sdc‐1 and epithelial mesenchymal transition (EMT), proteolysis and the Rho kinase pathway. Analysis of gene expression data of the TNMplot.com database revealed that Sdc‐1 expression was higher in primary breast tumours compared to metastases. The impact of Sdc‐1‐depletion on the cellular phenotype was investigated in a Matrigel‐based three‐dimensional cell culture model. Sdc‐1 depletion resulted in the formation of larger spheroids and the formation of invasive protrusions. Application of matrix metalloproteinase (MMP) and Rho kinase inhibitors could block the Sdc‐1‐induced phenotype. qPCR analysis of Sdc‐1‐depleted cells in two‐dimensional culture revealed upregulated expression of the EMT‐markers CDH1, FN‐1, CLDN1, the proteolysis markers MMP3, and MMP9, and HPSE, while MMP2, VIM and ROCK‐2 were downregulated. Immunocytochemistry confirmed upregulation of MMP9 and fibronectin, the latter being particular prominent after ROCK inhibition. STRING analysis confirmed an interaction of the investigated gene products at the protein level. Our results suggest that diminished Sdc‐1 expression plays a role in DCIS progression to IBC through deregulation of proteolytic factors and a partial EMT.